Mapping the accounting office's operational process: an analysis of the accountant-manager's intervention in the business - Milanesi Trindade, Nadine (2024)
Structured operational methods enable the initiation and continuity of tasks performed in the routine of the accounting office. In this way, it makes it possible to visualize the leader's action in relation to organizational processes. In view of this, it enables the optimization of time and activity planning, promotes flexibility and agility for process adjustments and avoids errors and rework. In the present study, the objective is to analyze the role of the accounting manager in mapping operational processes, his leadership actions in the process of involving procedural activities. To improve the visualization of the process, the Flowchart tool was used, which has in its structural and operational characteristics the attendance of the accounting services offered. The main point of improvement is the connectivity between the leader and employees in view of the main attributes that make the organization's structure viable: mission, vision and values.